Analisis Kebutuhan Air Bersih Domestik Desa Karang Anyar Daerah Layanan PDAM Kota Sumenep - Rahmanto, Ach. Desmantri; Zainah, Nor (Fakultas Teknik, Universitas Wiraraja, 2025)
The need for clean water provision and service from time to time is increasing which is sometimes not balanced by service capacity. This increase in demand is caused by an increase in population, an increase in the standard of living of residents, as well as the development of cities/service areas or things related to improving the socio-economic conditions of residents which are accompanied by an increase in the amount of water needs per capita. In order to meet the increasing need for clean water, where the discharge of water sources is decreasing every year, the regional drinking water company (PDAM) of Sumenep Regency It is necessary to review the need for clean water for the eastern region, especially Karang Anyar Village, Kalianget District, Sumenep Regency in the future. The purpose of this study is to determine the clean water needs of the Karang Anyar Village community for the next 25 years. The data analysis technique used in this study is the projection of the number of customers up to 25 years and the projection of the amount of water needs up to 25 years. The need for domestic clean water in Karang Anyar Village for the next 5 years is 0.71296 l/second, for the next 10 years it is 0.82639 l/second, for the next 15 years it is 0.95602 l/second, for the next 20 years it is 1.10764 l/second, and for the next 25 years it is 1.28125 l/second. The estimated need for domestic clean water production for the next 5 years is 10,489 l/day, for the next 10 years it is 12,694 l/day, for the next 15 years it is 14,900 l/day, for the next 20 years it is 17,547 l/day, and for the next 25 years it is 19,750 l/day.